Santri social mobility in the formation of identity: A bildungsroman analysis of Ahmad Fuadi’s Negeri 5 Menara Trilogy - Amin, Muhammad Al; Adji, Muhamad; Hidayatullah, Moch. Irfan (Universitas Muhammadiyah Malang, 2026)
This study looks at how social mobility shapes the protagonist’s identity in Ahmad Fuadi’s ‘Negeri 5 Menara’ trilogy. Most earlier studies on these novels focus on moral values or educational motivation. But few have asked how the protagonist’s social mobility relates to his identity formation. But identity matters more than ever in today’s changing Indonesia. Educational mobility is growing. People interact across cultures more often. And globalization keeps shaping who young people become. Within this broader landscape of global educational mobility, literary works such as the Negeri 5 Menara trilogy portray the identity formation of Indonesian Muslim youth who experience both class and cultural mobility. This research aims to reveal the construction of a santri identity through the representation of social mobility experienced by the protagonist by employing a Bildungsroman analytical framework. The study applies a qualitative descriptive method with an objective approach to literary texts as conceptualized by M. H. Abrams. The unit of analysis consists of narrative events that represent the protagonist’s social mobility. The primary data source is the Negeri 5 Menara trilogy, which is examined through critical reading of the protagonist’s developmental trajectory across three stages of identity formation: the initial crisis phase, the phase of conflict and educational formation, and the stage of maturity. The findings indicate that Alif’s social mobility extends beyond geographical movement and also encompasses cultural mobility shaped by educational experiences, cross-cultural interactions, and engagement within global networks. These experiences contribute to the formation of a dynamic and cosmopolitan santri identity, tell us about cosmopolitan Muslim literacy on Alif’s experiences moving for school, living as an intellectual away from home, show that being a santri doesn’t have to mean being closed off. It can become more open and adaptive. These findings contribute to literary studies, identity studies, and cultural studies by offering a deeper understanding of how the identities of Muslim youth are shaped within the context of contemporary society. Penelitian ini mengkaji representasi mobilitas sosial dalam pembentukan identitas tokoh utama pada trilogi novel ‘Negeri 5 Menara’ karya Ahmad Fuadi. Selama ini karya tersebut lebih sering dikaji dari perspektif nilai moral dan pendidikan, sementara relasi antara mobilitas sosial tokoh dan proses pembentukan identitas diri masih jarang mendapat perhatian. Padahal isu identitas menjadi penting dalam konteks perubahan sosial Indonesia yang ditandai oleh meningkatnya mobilitas pendidikan, interaksi lintas budaya, serta dinamika globalisasi yang memengaruhi pembentukan identitas generasi muda. Di tengah dinamika pendidikan global tersebut, karya sastra seperti trilogi Negeri 5 Menara menampilkan proses pembentukan identitas generasi muda Muslim Indonesia yang mengalami mobilitas kelas dan budaya. Penelitian ini bertujuan untuk mengungkap konstruksi identitas santri melalui representasi mobilitas sosial tokoh utama dengan menggunakan pendekatan analisis Bildungsroman. Metode yang digunakan adalah metode deskriptif kualitatif dengan pendekatan objektif terhadap teks sastra sebagaimana dikemukakan oleh M. H. Abrams. Unit analisis penelitian berupa peristiwa naratif yang merepresentasikan mobilitas sosial tokoh utama. Sumber data primer berupa teks trilogi Negeri 5 Menara yang dianalisis melalui teknik pembacaan kritis terhadap perkembangan tokoh dalam tiga tahap pembentukan identitas, yaitu fase krisis awal, fase konflik dan proses pendidikan, serta fase kedewasaan. Hasil penelitian menunjukkan bahwa mobilitas sosial tokoh Alif tidak hanya berupa perpindahan geografis, tetapi juga mencakup mobilitas kultural melalui pengalaman pendidikan, interaksi lintas budaya, dan keterlibatan dalam jejaring global. Proses tersebut membentuk identitas santri yang dinamis dan kosmopolitan. Dalam konteks wacana literasi Muslim kosmopolitan, pengalaman mobilitas pendidikan dan diaspora intelektual yang dialami tokoh memperlihatkan bahwa identitas santri dapat berkembang menjadi lebih terbuka dan adaptif. Temuan ini memberikan kontribusi bagi kajian sastra, identitas, dan studi budaya dalam memahami pembentukan identitas generasi muda Muslim dalam masyarakat modern.